Energy cost differences between marathon runners and soccer players: Constant versus shuttle running - Padulo, Johnny; Buglione, Antonio; Larion, Alin; Esposito, Fabio; Doria, Christian; Čular, Dražen; di Prampero, Pietro Enrico; Peyré-Tartaruga, Leonardo Alexandre (Frontiers in Physiology, 2023)
Purpose. In the last decades, the energy cost assessment provided new insight on shuttle or constant running as training modalities. No study, though, quantified the benefit of constant/shuttle running in soccer-players and runners. Therefore, the aim of this study was to clarify if marathon runners and soccer players present specific energy cost values related to their training experience performing constant and shuttle running. Methods. To this aim, 8 runners (age 34±7.30y; training experience 5.70±0.84y) and 8 soccer-players (age 18.38±0.52y; training experience 5.75±1.84y) were assessed randomly for 6’ on shuttle-running or constant-running with three days of recovery in-between. For each condition, the blood lactate (BL) and the energy cost of constant (Cr) and shuttle running (CSh) was determined. To assess differences for metabolic demand in terms of Cr, CSh and BL over the two running conditions on the two groups a MANOVA was used. Results. V̇O2max were 67.9±4.5 and 56.8±4.3 ml·min·-1·kg-1 (p=0.0002) for marathon runners and soccer players, respectively. On constant running, the runners had a lower Cr compared to soccer players (3.86±0.16 J·kg-1·m-1 vs 4.19±0.26 J·kg-1·m-1; F=9.759, respectively; p=0.007). On shuttle running, runners had a higher CSh compared to soccer players (8.66±0.60 J·kg-1·m-1 vs 7.86±0.51 J·kg-1·m-1; F=8.282, respectively; with p=0.012). BL on constant running was lower in runners compared to soccer players (1.06±0.07 mmol·L-1 vs 1.56±0.42 mmol·L-1, respectively; with p=0.005). Conversely, BL on shuttle running was higher in runners compared to soccer players 7.99±1.49 mmol·L-1 vs 6.04±1.69 mmol·L-1, respectively; with p=0.028).